SHM_1308346_HST_3D Thin-Butted Flint Axe - National Historical Museums (National Historical Museums, 2026)
Structured Light 3D model of a thin-butted flint axe from the Swedish Neolithic, collected in the field from Hallsberg Parish in Närke and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=397

Link to Sök I Samlingarna

https://samlingar.shm.se/object/BE5A5749-39FB-4841-ADC3-9CFC86343577
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Dynamic Collections; 3D Model; Museum Object; Hallsberg; Swedish Neolithic; Swedish Early Neolithic; Swedish Middle Neolithic; Structured Light Scanning; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi